Unseen Drivers of Antimicrobial Resistance: The Role of Industrial Agriculture and Climate Change in This Global Health Crisis - Madeline E. Graham; Brenda A. Wilson; Davendra Ramkumar; Holly Rosencranz; Japhia Ramkumar (Challenges)
Antimicrobial resistance (AMR) is an urgent global health threat with many anthropogenic drivers outside of healthcare. The impacts of modern agriculture on human health are manifold, from the food systems and dietary patterns they support to the less apparent effects of environmental stresses and biodiversity loss in ecosystems. Intensive practices, such as chemical fertilizers, pesticides, and herbicides, induce abiotic stresses that deplete biodiversity and drive AMR in soil and aquatic microbiomes. The overuse of antibiotics in livestock production is another major driver of AMR. Changes in weather patterns due to climate change have the potential to exacerbate these issues as warmer and wetter weather increases the potential for bacterial infection. While practices exist to address healthcare-associated drivers, the impact of agriculture and environmental destruction are not widely appreciated in healthcare and biomedical sciences. It is imperative that healthcare professionals and public health experts understand these connections to properly address the emergent issue of AMR. This review aims to summarize the current data on important agricultural and environmental drivers of AMR for educational purposes, to fill gaps in knowledge, and to improve current practices and stimulate further research.